PENDUGAAN VOLUME BATANG BEBAS CABANG POHON BERDIRI JATI PLUS PERHUTANI UMUR 6 SAMPAI 11 TAHUN DI KPH MADIUN - , RACHMASARI M S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Jati plus perhutani (JPP) produced by Perhutani is superior teak. It is derived from tree breeding programs. JPP from Clonal Seed Orchard (CSO) was developed in Madiun Forest District in 2002. However, quantitative information about the JPP stands potency in KPH level is inadequate. The aim of the research is to obtain an estimated tree volume model for JPP with the age between 6 to 11 years. It is expected that this information can be used to support forest planning, sustainability and development strategic in the management of JPP forest. The research was conducted in 5 Sub Forest Districts (BKPH) of Madiun Forest District (KPH Madiun) in Perhutani Unit II of East Java in September 2013 for two weeks. The research used dominant trees in 6-11 years JPP stands as the sample located in the best compartments. The measured parameters of each trees is tree height, crown base height, milestones diameter, diameter at breast height, and diameter measurements which measured every 2 meters up to crown base. To compose the clear bole volume model used 480 samples of trees with variables such as stand age. The result showed that S model can be used to estimate the volume of 6 to 11 years JPP stands and to describe the growth model at young stands. S model in mathematic form is : V= e(-0.0003 + -20.8319/x) with a standard error of the estimate 0.100, the coefficient determination is (R2) 0.977 and the coefficient of corrected determination is (Radj2) 0,972. The value showed that the equational model are significant and can be used to estimate the clear bole volume of JPP standing trees.